Dieta natural de espécies do gênero Macrobrachium (Crustacea, Decapoda) com ocorrência no Cerrado - Cruz, Barbara Regina Fernandes da (2020)
The knowledge about the species' diet is essential to provide information about the population growth and maintenance in the natural environment. The species Macrobrachium amazonicum and Macrobrachium brasiliense are freshwater shrimp species widely distributed in Brazil, with commercial importance for human consumption and in aquarium. The aim of this study was to evaluate the natural diet of populations of M. amazonicum e and M. brasiliense, comparing the diets of both species according to sex, sampling period and body size. Sampling was carried out between September 2018 and August 2019. The individuals collected had their sex determined and cephalothorax measured. Stomach content was evaluated based on the degree of repletion, the method of points and the frequency of occurrence. High frequency of plant material was found in the stomachs of both species. There were no significant differences of diet between males and females and between the two sampling periods (dry and rainy). It was observed that large M. amazonicum (6,14 |-- 8,71 cm) individuals fed less on plant material and more on insects while M. brasiliense of large size (5,29 |-- 7,56 cm) had a more balanced diet, with intermediate or high frequency of all items. The results obtained indicate that both species have an omnivorous diet, with less variety for M. amazonicum, and suggest that the composition and proportion of items could vary considerably depending on availability and environmental characteristics.